THE UTILIZATION OF INTEGRATED MARKETING COMMUNICATION TO IMPROVE PRODUCT SELLING BASED ON BUYER'S PERSPECTIVE - R Suryani, Nirmala
Small and Medium Business Enterprises hold a major role in both the developing and the developed countries to improve economic growth. In order for the Small and Medium Enterprises to have a sustainable business, there must be an alignment in product-centric and customer-centric development. Finding out the right customers for the product will give chances for the company to get validation from the problem and feedback to construct the solution. It also helps the company to acquire potential buyers that will lead to many repeatable sales and eventually support the company to be superior in the industry. In order to ensure that the market is well-educated about the well-developed product or service’s existence, quality attributes, benefits, efficacy, and the engagement of an effective integrated marketing communication must be applied. The integrated marketing communications mix is a comprehensive marketing communication plan that combines and evaluates a variety of strategic communication disciplines – general advertising, personal selling, sales promotion, direct marketing, public relations, sponsorships and others, to provide clarity, consistency and maximum communication impact. It can be classified as online marketing and offline marketing, after analyzing the customer buying journey. It develops costumer’s trust and creates the brand equity. The company’s growth can be seen significantly when the Integrated Marketing Communication is applied successfully. One of the benefits is the improvement in products selling and company performances. Since customers are well-informed, they will have a better understanding of the product and have more interest in the product because of the utilization of IMC. The study was conducted based on a qualitative method in collecting the data where in-depth and semi-structured interview were the tools. In analyzing the data, content analysis and pattern matching analysis were used. The interview processes with the samples of buyer personas were the main core in order to create effective Integrated Marketing Communication, especially to know the customer journey. The variables that were validated were taken from the Business Model Canvas and Marketing Mix. This study finding are the right buyer personas for the business, Business Model Canvas, Marketing Mixed, and Integrated Marketing Communication’s further implementation plans based on the input from each cluster of buyer personas. The findings were applied to the author’s fashion-based business, Liyamsé, to validate the product, to gain deeper knowledge about the buyers, and to create effective Integrated Marketing Communication strategies.